1999
DOI: 10.1046/j.1523-1739.1999.013002327.x
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Success of a Neotropical Migrant in a Multiple‐Use, Forested Landscape

Abstract: We studied the nesting success of an individually marked population of Kentucky Warblers (Oporornis formosus), a species that nests in disturbed and undisturbed forests, in a heterogeneous, managed forest site in the Shawnee National Forest in southern Illinois from 1992 to 1995. We examined the effects of forest stand type (clearcuts of various ages, tree plantations, and older forest) and distance from habitat edges on rates of nest predation and brood parasitism by Brown‐headed Cowbirds (  Molothrus ater). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 39 publications
8
33
2
Order By: Relevance
“…For forest avifauna this depends largely on mobility (Lens et al, 2002), home range/territory size (Rolstad, 1991) and migratory patterns (Morse & Robinson, 1999), as well as lifehistory traits and demography (Recher et al, 1987;Hansen & Urban, 1992;Warburton, 1997;Dale, 2001;Beier, Van Drielen & Kankam, 2002). Many traits have been identified as associated with local extinction proneness in populations of forest-dependent birds in fragmented landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…For forest avifauna this depends largely on mobility (Lens et al, 2002), home range/territory size (Rolstad, 1991) and migratory patterns (Morse & Robinson, 1999), as well as lifehistory traits and demography (Recher et al, 1987;Hansen & Urban, 1992;Warburton, 1997;Dale, 2001;Beier, Van Drielen & Kankam, 2002). Many traits have been identified as associated with local extinction proneness in populations of forest-dependent birds in fragmented landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, King et al (1996) reported that Ovenbirds near edges compensate for increased predation by renesting. In contrast, Morse and Robinson (1999) found that Kentucky Warbler (Oporornis formosis) productivity is lower in agricultural edge than interior areas.…”
Section: Distribution Of Breeders In Relation To Habitat Qualitymentioning
confidence: 85%
“…Many studies have compared habitats that contrasted strongly in terms of vegetation structure and composition or fragment size. Few studies have examined how proximity to edge influences habitat quality in a relatively unfragmented forest landscape (although see King et al 1996King et al , 1998aMorse & Robinson 1999).…”
Section: Breeding Distribution and Demographymentioning
confidence: 99%
See 1 more Smart Citation
“…Schmidt and J. Goheen, unpublished manuscript). Habitats often have predictably higher quality, on average, than others (wintering habitat: Marra et al 1998;breeding habitat: Holmes et al 1996, Morse andRobinson 1999). Birds may therefore disperse between habitat types between and/or within years, biasing settlement toward higher quality habitats.…”
Section: Caveats and Future Directionsmentioning
confidence: 99%